Masticatory performance of complete denture wearers after using two adhesives: a crossover randomized clinical trial - Oliveira Junior, Norberto Martins de [UNESP]; Rodriguez, Larissa Santana [UNESP]; Mendoza Marin, Danny Omar [UNESP]; Paleari, André Gustavo [UNESP]; Pero, Ana Carolina [UNESP]; Compagnoni, Marco Antonio [UNESP] (Elsevier, 2014)
Statement of problem Masticatory performance analysis of conventional complete denture wearers who use denture adhesives is scarce in the dental literature. Purpose The purpose of this study was to assess the effect of the use of 2 denture adhesives on the masticatory performance of conventional complete denture wearers by means of a crossover study. Material and methods Forty individuals who were edentulous received new maxillary and mandibular complete dentures, and, after an adaptation period, were submitted to masticatory performance analysis without denture adhesive (control). The participants were randomly divided and assigned to 2 protocols: protocol 1, denture adhesive 1 (Ultra Corega cream tasteless) use during the first 15 days, followed by no use of denture adhesive over the next 15 days (washout), and then use of denture adhesive 2 (Ultra Corega powder tasteless) for 15 days; protocol 2, denture adhesive 2 (Ultra Corega powder tasteless) use during the first 15 days, followed by no use of denture adhesive during the next 15 days (washout), and then use of denture adhesive 1 (Ultra Corega cream tasteless) for 15 days. The masticatory performance was assessed immediately after the use of denture adhesive by means of the sieve method, in which participants were instructed to deliberately chew 5 almonds for 20 chewing strokes. Masticatory performance was calculated by the weight of comminuted material that passed through the sieves. Data were analyzed by a 1-way ANOVA for paired samples and the multiple comparison of means by using the Bonferroni test (α=.05). Results A significant increase in masticatory performance was noted after using the Ultra Corega cream (mean, 32.6%) and Ultra Corega powder (mean, 31.2%) when compared with the control group (mean, 19.8%) (P<.001). No significant difference was found between the 2 denture adhesives evaluated. Conclusion The use of denture adhesive improved the masticatory performance of conventional complete denture wearers. No difference was found in masticatory performance with the use of cream or powder denture adhesive.